Staff preparedness to implement mobile technologies in libraries - Saravani, S.; Haddow, Gaby (Facet Publishing, 2012)
Mobile technologies have added a new dimension to the role of library staff, a role that requires relevant knowledge and skills to ensure that the needs and expectations of clients are met {Gentry, 2011; Kroski, 2008; Traxler, 2008). For libraries to succeed in the mobile environment, management will have to consider two significant staffing issues. Firstly, it needs to understand the knowledge and skills required by staff to enable them to deliver services through mobile technologies; secondly, that understanding should be applied to develop support and training for staff in the use of mobile technologies. In order to explore these issues a survey was undertaken in late 2010, involving librarians working in the vocational education and training (VET - similar to further education in the UK) sector in Australia and New Zealand